Nurses navigating moral distress, resilience, and team dynamics: A literature review - Ansari, Natasha (Nursing ethics, 2025)
BackgroundThis manuscript explores the pervasive issue of moral distress among nurses and its impact on their well-being and professional satisfaction. Focusing on diverse factors contributing to moral distress, the review spans various experience levels and patient care settings.MethodUtilizing integrative reviews and sourcing from PubMed, CINAHL, SCOPUS, PsycINFO, and ProQuest, the study synthesizes findings from studies worldwide. The conceptual framework by Whittemore & Knafl is employed to comprehensively analyze nurses’ experiences.ResultsKey factors were identified as contributing to moral distress, including concerns about care quality, team dynamics, and insufficient support. Interventions range from light-touch approaches like mentorship programs to resource-intensive strategies such as staff wellness initiatives. The impact of the COVID-19 pandemic on nurses’ moral distress is also explored.ConclusionMoral distress in nurses leads to burnout and, in some cases, prompts professionals to leave the field. The study emphasizes the need for organizational-level initiatives, support networks, and interventions to address moral distress. Identified gaps in the literature underscore opportunities for future research to better prepare clinicians and advance understanding across experience levels and settings.